Giant pedunculated hepatocellular adenoma masquerading as a subdiaphragmatic mass: Diagnostic challenges of a rare tumor - Zahra Shafaee, MD, MBA; Shaojun Liu, MD, PhD; Maria Isabel Fiel, MD; Robert Blue, MD (Radiology Case Reports, 2021)
Giant pedunculated hepatocellular adenomas are extremely rare tumors and often detected incidentally on cross-sectional imaging studies. We report the case of a 34-year-old woman who underwent cross-sectional imaging for staging evaluation of a uterine tumor. A large left subdiaphragmatic mass, without clear connection to the liver, was seen prompting diagnostic laparoscopy; during which a large pedunculated mass attached to the left lobe of the liver was found and resected. This case report highlights the challenges and pitfalls in the imaging diagnosis of pedunculated hepatocellular adenomas, such as difficulty in characterizing the mass or inability to identify the vascular attachment to the liver. Image-guided biopsy and diagnostic laparoscopy are valuable tools to establish diagnosis; most of these lesions are amenable to laparoscopic resection.